Urinary Stone Location with Ureteral Stents in Place: Always on the Move, and not Where you Would Expect - Pratsinis, Manolis; Tekin, Ahmet Cevdet; Zumstein, Valentin; Güsewell, Sabine; Schmid, Hans-Peter; Abt, Dominik; Betschart, Patrick (Urology Journal, 2020)
Purpose: To assess migration of urinary stones with ureteral stents in place. Materials and Methods: We performed a retrospective analysis of stone characteristics and locations in patients treated with secondary retrograde intrarenal surgery for symptomatic urinary stones at our institution. We analyzed 393 patients with a median age of 53 years and a median stone size of 7 mm. Stone location was assessed at ureteral stent insertion and four weeks later prior to stent removal and retrograde intrarenal surgery (RIRS). Results: Migration of urinary stones was seen in 33.1% of the patients with an indwelling ureteral stent. Stones with caudal migration were smaller for any given initial position. 7.1% of the stones were located at one of the three sites of narrowing at initial presentation, this percentage increased to 18.8% at the time of stone extraction. Stone composition did not affect stone migration. Conclusion: Radiographic imaging prior to retrograde intrarenal surgery is recommended due to the migration of urinary stones with indwelling ureteral stents. The most appropriate surgical approach can be devised depending on stone localization.